2009
DOI: 10.1017/s1751731109990413
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a quantitative trait locus for increased muscularity on carcass traits measured by subjective conformation and fat class scores and video image analysis in crossbred lambs

Abstract: A quantitative trait locus (QTL) for increased loin muscularity (TM-QTL) has previously been identified in purebred Texel sheep. Crossbred lambs born out of Mule ewes mated to heterozygous Texel sires for the TM-QTL were evaluated for a range of carcass traits. Lambs were genotyped and classified as carriers (n 5 62) of a single copy of the TM-QTL and non-carriers (n 5 49). In this study, the effects of the TM-QTL on carcass attributes were investigated using subjective classification scores for conformation a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2009
2009
2014
2014

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 30 publications
(31 reference statements)
1
4
0
Order By: Relevance
“…This result is similar to that reported for TM-QTL by Rius-Vilarrasa et al (2009b), who found that crossbred lambs from a similar genetic background to those in our study carrying one copy of TM-QTL showed no significant difference in conformation and fat class scores compared with non-carriers. The results of this study indicate that the current industry carcass evaluation system would not be able to detect the improvement in loin muscle characteristics offered by LM-QTL.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…This result is similar to that reported for TM-QTL by Rius-Vilarrasa et al (2009b), who found that crossbred lambs from a similar genetic background to those in our study carrying one copy of TM-QTL showed no significant difference in conformation and fat class scores compared with non-carriers. The results of this study indicate that the current industry carcass evaluation system would not be able to detect the improvement in loin muscle characteristics offered by LM-QTL.…”
Section: Discussionsupporting
confidence: 92%
“…Rius Vilarrasa et al (2009a) reported that VIA achieved consistently higher accuracy and precision in predicting the carcass primal cut weights and SMY compared with the MLC classification grading for carcass conformation and fat class, which is in use in UK abattoirs. Rius-Vilarrasa et al (2009b) didnot detect significant difference in VIA-predicted loin dimensions and primal cut weights between TM-QTL carrier and non-carrier lambs using the standard prediction equation produced by E 1 V Technology, Germany. By contrast, deriving refined prediction equations by calibration against CT measurements it was possible in this previous experiment to detect a significant increase in MLL depth in TM-QTL carrier lambs.…”
Section: Discussionmentioning
confidence: 84%
See 2 more Smart Citations
“…In Texel and Texel–Suffolk families another confirmed muscling QTL (TM-QTL) was localized to 2 cM telomeric of the same marker (CSSM18) on OAR18 (Walling et al, 2004; Macfarlane et al, 2009, 2012; Rius-Vilarrasa et al, 2009; Matika et al, 2010). The muscling phenotype in these animals was similar to that in the Poll Dorset sheep and associated with altered muscle shape–the carcass was described as more “compact.” It was recently concluded there is evidence for imprinting of this QTL.…”
Section: Confirmed Quantitative Trait Loci For Muscling In Sheepmentioning
confidence: 99%